Causes and Strategies for Overcoming Work Stress (A Case Study on PT. Bank Rakyat Indonesia Tbk Tondano Branch Office) - Novita Paramita Motoda; Rahel Widiawati Kimbal (International Journal of Applied Business and International Management, 2020)
This study aims to determine the factors that give rise to work stress on the employees of PT Bank Rakyat Indonesia Tondano Branch Office, and propose effective strategies to overcome it. This research applied qualitative methodology by interview, observation, and documentation for data collection. The data were analyzed using the Miles and Huberman model. The study was conducted in Tondano. The study findings indicate that work stress is attributable to several factors such as (a) conflicts with coworkers due to argumentations, (b) targeted and heavy workload, and (c), ill-adjusted work times. Therefore, the management's strategies to overcome it necessary to unveil are: (1) creating a flexible work atmosphere, (2) paying attention to employee's complaints, (3) encouraging employees by giving rewards, (4) making recreational program, (5) performing regular work rotations. Furthermore, the employees need to: (1) have short in-room break, (2) take a part in outdoor activities or enjoy hobbies on vacation, (3) improve quality work, (3) find suitable working partners able to create a cheerful atmosphere, and (4) improve quality work. The conclusion ends with a final comment that: (1) work conflict occurs when heated arguments arise among employees affecting their mental condition in carrying out their jobs, (2) excessive targeted workload makes them fall into depression since they are working around the clock, and (3) irregular working hours saps their energy since overmuch office hours lessens their family time.